The preoperative testing at laboratories in Najaf are being performed on patients at the time of the surgery in order to do this evaluation of blood-borne viruses - Khzal, Alaa Mahdy obaid (PT. Antis International Publisher, 2024)
Al-Sadir Teaching Hospital, Najaf, Iraq was the surrounding for this study that was done during the window of time from the 1st of January to the 1st of November of the same year. A descriptive, cross-sectional, hospital-based study of hospitals is investigated. The research was conducted during January, 1st 2023 and November 1, 2023 in the course of studies. The project evlaution was launched on 21st of January and finalized on 1st of November. The purpose of this researched was to determine proportion of patients who were infected with the blood borne diseases such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV). All of these viruses are transmitted because the blood carries them. The technique was considered necessary to establish the amount of viral infection in these patients. ELISA testing was among the components, of the pre- surgical virus therapy, which was received by the patient and it was performed on the blood samples collected from the patient.Eventually we came to the conclusion that the procedures were applied as implied in the system. In our investigations, we determined that the Human Papilloma Virus (HPV) is the one virus that had been identified to be infecting the people whose cases were detected by the examination process. The second most well-known virus after Human Virus (HCV) that is also categorized as one of the human viruses is the Human and Human Immune Globaly Viruses complex (HIV). I state emphatically discrimination or age bias was non existent during data collection at any point in time of the whole process. I got the data together in a process which of a ten months' duration and took place solely in this particular educational organization. A total of 125 individuals were tested positive out of which 64 were affected by HBV, 60 (60%) got affected by HCV, and 7 (70%) were affected by HIV. The isolation of the virus was only possible when it was passed on by all male who were tested. The girls had a unique and admirable quality: not a single one of them tested positive for the infection. It was evident among the people affected that about two thirds were male. Actually, only less than 1/3 (30%) of the females getting tested HIV positive, whereas 5 (43.4%) of them had HBV and even 5 (45%) of them showed the HCV result Thus, it is evident with the result seen that the number of cases of women from prevention to men who visited the health center was much lower. We look forward to having 19,925 folks at the donation drive having filled up the collection tubes with their blood. Via the study of a total of 1,330 Hepatitis B virus cases, the test was found positive in (145) of them, and negative only in the (1205) remaining cases. By which implies gives us 19925 which is definitely it is the quantity of blood to be collected